(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
In this article, we delve into the intricate relationship between the agrarian sector and a country’s exports, employing modeling techniques to analyze the dynamics, determinants, and implications of this crucial linkage. Drawing upon a synthesis of economic theory, empirical research, and policy insights, our study aims to shed light on the mechanisms through which the agrarian sector influences a country’s export performance and vice versa.